2010
DOI: 10.1016/j.ntt.2010.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Repeated courses of antenatal corticosteroids: Are there effects on the infant's auditory brainstem responses?

Abstract: Our objective was to assess the effects of repeated antenatal corticosteroid treatments on the neonatal auditory brainstem response (ABR), a sensitive measure of neonatal brain maturity and auditory function. To achieve this, we performed and blindly evaluated neonatal ABRs on a subset of infants delivering within a multicenter randomized placebo-controlled clinical trial comparing single versus repeated courses of antenatal corticosteroid treatments for women at 23–31 weeks gestation who remained at increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…According to Waters et al ,29 antenatal steroid exposure did not affect hearing screen outcomes in VLBW infants. Multiple courses compared with a single course of betamethasone did not impact ABRs in exposed infants30 31 or hearing outcomes at age 5 years 32. However, Lee et al 33 observed that prenatal betamethasone reduced the risk for hearing impairment, but prenatal dexamethasone increased the risk for hearing impairment at 18–22 months’ adjusted age in extremely low birthweight infants.…”
Section: Discussionmentioning
confidence: 96%
“…According to Waters et al ,29 antenatal steroid exposure did not affect hearing screen outcomes in VLBW infants. Multiple courses compared with a single course of betamethasone did not impact ABRs in exposed infants30 31 or hearing outcomes at age 5 years 32. However, Lee et al 33 observed that prenatal betamethasone reduced the risk for hearing impairment, but prenatal dexamethasone increased the risk for hearing impairment at 18–22 months’ adjusted age in extremely low birthweight infants.…”
Section: Discussionmentioning
confidence: 96%
“…In one regimen, AC therapy is given only once; whereas in the others, AC therapy is repeated weekly [19,95,96], biweekly [1] or twice [3] from as early as 23 weeks to as late as 32 weeks of gestation. Some pregnant women have received as many as 9 treatment courses of 2 injections per course for a total of 18 AC injections [19,95,96]. Yet, there is concern that repeated AC treatment harms infant development if too much is given [67].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, there is concern that repeated AC treatment harms infant development if too much is given [67]. For example, human studies found that repeated AC treatments reduced birth weights and/or head circumferences [19,35,95,96], reduced brain cortex convolutions [65], decreased placental growth [83], increased the incidence of cerebral palsy [95], and caused attention problems at 2 years of age [25]. One study reported that merely two AC courses perturbed respiratory adaptation in preterm infants [70].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations